PENGARUH PAD, DAU, DAK, DBH, DAN BELANJA DAERAH TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN DAERAH TERTINGGAL - Rendy Alvaro (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2022)
This study aims to examine and analyze the effect of local revenue, general allocation fund, revenue sharing fund, specific allocation fund, expenditures for goods and services, capital expenditures, and regional funds for education affairs on economic growth in district regions of undeveloped regions in Indonesia. Research data uses secondary data obtained from the Ministry of Finance DJPK and BPS. The method uses panel data regression analysis using data from 2015-2019 in 122 Disadvantaged Regions in Indonesia. The results of this study indicate that the variables local revenue, general allocation fund, specific allocation fund, expenditures for goods and services, education affairs funds, and per capita income have a positive and significant effect. Meanwhile, the capital expenditure variable has a negative and significant effect, and Revenue Sharing Fund has no effect. The regression results show an adjusted R2 value of 0.9969, which means that the variables of economic growth can be explained by variations of the independent variables, namely local revenue, general allocation fund, revenue sharing fund, specific allocation fund, expenditures for goods and services, capital expenditures, regional funds for education amounting to 99,69 percent. While the remaining 0.31 percent is explained by other variables outside the model.